Analysis of Generic Structure and Grammatical Problem of Students in Writing English Paragraphs in Online Learning at Muhammadiyah University of Riau - Ardiya; Prih Febtiningsih (ELT-Lectura, 2022)
The purpose of this research is to find out the generic structure and grammatical problems encountered by the non-English students at Muhammadiyah University of Riau. The data was obtained through students writing task namely writing English paragraphs of descriptive text. The writing task was given through Learning System Management (LSM) of the university named Sikuli. The participants of this research were the Non-English students taking the English subject in the first semester in academic year of 2021/2022 at Muhammadiyah University of Riau. The samples of this research were 4 classes consisting of a number of students for each class taken randomly spreading in eight faculties. They were from Computer Science faculty (40), Communication Science faculty (28), Natural Science and Health faculty (45), and Teacher Training and Education faculty (25). The total number of students are 138. The researchers applied the theory of Gerot and Wignel (1994) and Halliday et al. (2014) from the perspective of systemic functional linguistics. In generic structure, the appropriateness and inappropriateness in formulating identification and descriptions in descriptive text were described. While, in grammatical case, the writing students were analyzed based on the theory proposed by Yarber and Yarber (2010) and Dye (2005). After the data was analyzed, the results were obtained. It was showed that the non-English students at Muhammadiyah University of Riau in writing English paragraphs of descriptive text got serious problem on writing identification (115/83%) as one of the generic structure in descriptive text. In addition, they also encountered grammatical problems such as noun, pronoun, verb, adjective, adverb, preposition, conjunction, parallelism, modifiers, subject-verb agreement, punctuation, and capitalization. Based on the numbers and the percentage of the grammatical problems above, it showed that the non-English students at Muhammadiyah University of Riau got serious problem on subject-verb agreement (129 / 14,16%). Keywords: Generic structure, Grammatical problems, Writing English paragraphs, Online learning